Electrochemical, spectroelectrochemical, electrocatalytic oxygen reducing, and heavy metal ion sensing properties of novel tetrakis-[4-((2, 8-bis (trifluoromethyl) quinolin-4-yl) oxyl)] substituted metallophthalocyanines - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN; ÖZER, METİN (ELSEVIER, 2022)
Novel tetrakis-[4-((2,8-bis(trifluoromethyl)quinolin-4-yl)oxyl)] substituted phthalocyanine complexes were obtained by the tetramerization reaction of corresponding phthalonitrile derivative with appropriate metal salts under determined conditions. The structures of the complexes were clarified by elemental analysis, fourier transform infrared, ultraviolet-visible and matrix-assisted laser desorption ionization time-of-flight mass spectroscopic methods. The redox properties of zinc, cobalt, and iron phthalocyanines were investigated by voltammetric and colorimetry supported in situ spectroelectrochemical measurements in non-aqueous solution medium. The metal and phthalocyanine ring based redox processes were observed to be associated with distinct spectral and color changes and affected by the presence of molecular oxygen in the medium. Furthermore, oxygen interaction measurements performed during the oxygenation of de-aerated electrolyte solution suggested that the iron phthalocyanine complex possesses oxygen binding capability and has the tendency of forming mu-oxo-dimer complexes and thus, displaying electrocatalytic activity for oxygen reduction reaction. Electrocatalytic oxygen reducing performances of the complexes were investigated in a medium similar to direct methanol or polymer electrolyte membraned fuel-cell working conditions and compared in detail. Iron(II) phthalocyanine complex appeared as suitable electrocatalyst for both polymer electrolyte membraned and direct methanol fuel cells with high catalytic performance towards oxygen reduction and high tolerance to methanol, respectively. The metallophthalocyanines modified quartz crystal microbalance sensors were designed to detect divalent heavy metal ions (cobalt(II), cadmium(II), cupper(II), and zinc(II)) in water samples. Frequency shift measurements of the complexes showed that the possibility of the use of iron(II) phthalocyanine as a novel cadmium(II) ion sensing material, owing to its high sensitivity, reversibility, stability, and the possibility to operate at room temperature. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Electrochemistry; Spectroelectrochemistry; Electrocatalysis; Oxygen reduction; Sensing material; CATALYTIC-ACTIVITY; BEARING COUMARIN; BIPHASIC SYSTEM; PHTHALOCYANINES; TETRA; COBALT(II); REDUCTION; CO(II); IRON; ADSORPTION